Does Unopposed Peri-menopausal or Post-menopausal Estrogen Protect against Breast Cancer? A Systematic Review - Joseph Loze Onwude (Journal of Surgery and Surgical Research - Peertechz Publications, 2021)
Globally, breast cancer is the most common incident cancer and cause of cancer deaths in women. The incidence of breast cancer suddenly increases from age 40 and continues to increase until age 84 years. These coincide with perimenopause and menopause periods.  Hormone Replacement Therapy (HRT) is recognized to cause breast cancer. This causal association has become assumed with unopposed Estrogen Replacement Therapy (ERT) which is used for women who require HRT but do not require the Progestogen component. This systematic review assessed the evidence behind the belief that unopposed ERT had a causal relationship with breast cancer. Established databases were searched to August 2017 for publications that examined the relationship between unopposed ERT and breast cancer in cohort studies (prospective and retrospective), case control studies and randomized controlled studies. Unopposed ERT could be oral, transdermal patch or gel, subcutaneous or intranasal routes. All the studies were systematically assessed for the risk of bias and the measures of effect such as appropriate measures of effect [relative risk for randomized controlled studies, incidence ratio/rate for prospective cohort studies and odds ratio for retrospective cohort studies and case control studies. The quality of the evidence was assessed with GRADE methods [1].  We report on the general direction of the evidence from different types of studies over different decades in different countries using different types of unopposed Estrogens at different doses, to show whether the evidence is consistent in its direction that unopposed Estrogens do not increase the risk of Breast cancer in peri-menopausal or post-menopausal women.  The evidence does not support that unopposed ERT increases the risk of breast cancer. Where an association has been reported, there was methodological association because the study was either a retrospective study as case control study or cohort study which are not study designs that are valid to show cause and effect relationships. Moreover the only randomized studies in the short term and long term show no cause and effect relationship.  The implication is that as unopposed ERT does not increase the risk of breast cancer, more women can consider its use and benefits.